Communicative Language Teaching (CLT) Implementation In Kurikulum Merdeka: A Lesson From English Teachers’ Voices - Lestari, Muji Budi; Margana, Margana (Universitas Pendidikan Mandalika, 2024)
This study examines the implementation of Communicative Language Teaching (CLT) within the Kurikulum Merdeka framework in Gowa District, Indonesia, focusing on English teachers' experiences and strategies. Using qualitative methods, including surveys (n=12), focus group discussions (n=7), and in-depth interviews (n=2), the study identifies challenges such as limited vocabulary, uneven proficiency levels, and insufficient resources. Strategies to overcome these challenges include promoting peer communication, leveraging multimedia resources, and fostering parental involvement. Comparisons with curriculum reforms in South Korea, Japan, and Bangladesh provide a global perspective on CLT implementation.The findings highlight the positive impact of CLT on students' communicative competence and suggest that Kurikulum Merdeka's focus on independent learning and project-based initiatives, along with collaborative activities such as English day, clubs, camps, and competitions, can further support CLT. However, effective execution, continuous evaluation, and addressing diverse educational backgrounds and regional disparities are essential for achieving the desired English proficiency outcomes. This study offers valuable insights for policymakers, educators, and researchers to enhance English language teaching in diverse educational settings.